The Factors affecting urban art development in the Mekong Delta, Viet Nam - Dang, Pham Cam; Minh, Vo Quang (Street Art & Urban Creativity, 2024)
The study’s objective is to evaluate the state of art’s development in Mekong Delta urban regions in Vietnam. The results from 150 interview forms identified two groups of factors, including type and historical-cultural value with 12 variables; order and community interaction with 9 variables. With a coefficient of KMO = 0.94 and a total variance of 67.02%, types include trees, lights, construction works, statues, and paintings, distributed in parks, squares, main roads, government agencies, and private establishments. There is a difference in people’s interest in urban art in 3 types of cities. Urban art in urban areas is assessed to meet people’s needs.